Prosedur Penyelesaikan Klaim Asuransi Takaful Dana Pendidikan (Fulkandi) Pada PT. Asuransi Takaful Keluarga Cabang Palembang - Ayu Gemi Nastiti; Fadilla Fadilla (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2018)
This study aims to determine the procedure for settling claims for education fund takaful insurance as well as to determine the factors of obstacles faced and how to overcome the obstacles that occur when submitting claims at PT Asuransi Takaful Keluarga Palembang Branch. In this paper, the author uses field research with qualitative data types using one data source, namely primary data. Data collection techniques are carried out by interviews and documentation that can answer existing problems, and so the data is analyzed in a quantitative descriptive manner. From this study, the procedure for settling claims for Takaful insurance on education funds on family takaful insurance for Palembang branch is quite simple, if the perseta can submit a claim through an agent or agent or come to the office, participants must complete the data from the requirements of the claim document, after the insurance officer documents are complete. will submit a claim to the service office will provide data to the head office and if the data is correct, the head office will verify and the claim can be sent to the participant's account.